PENGARUH MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SDN JELEKONG - Asep Priatna; Indriani Lestari; Acep Roni Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research is motivated by students in elementary schools who lack critical thinking skills. The purpose of this study is to find out how to influence and improve students' critical thinking skills after using the Problem Based Learning model for fifth grade students at SD Negeri Jelekong, Kp Ninerang, Jelekong Village, Baleendah District, Bandung Regency, Academic Year 2022/2023. Therefore the researcher was interested and took the title "The Influence of the Problem Based Learning Model in Improving the Critical Thinking Ability of Fifth Grade Students at Jelekong Elementary School." This study used a quantitative research type with a quasi-experimental method and nonequivalent control group design. On theme 8, sub-theme 3. The population used was all fifth grade students at SD Negeri Uglyong. VA class as the control class and VB class as the experimental class. Both classes will be given an initial test (pretest) and a final test (posttest). In this study using a test instrument in the form of multiple choice of 20 questions. The results of pretest data processing in the control class obtained an average of 55.17 with a standard deviation of 13.357 and the control class obtained an average value of 58.33 with a standard deviation of 16.522. The results of the posttest for the experimental class obtained a value of 83.67 with a standard deviation of 7.980 and the control class obtained a value of 56.00 with a standard deviation of 17.636. For the results of hypothesis testing using the t test obtained sig. (2-tailed) of 0.000. So it can be concluded that the ability of the Problem Based Learning model can improve the critical thinking skills of elementary school students.